Meningkatkan Mutu Pelayanan Pendidikan di KB PKK Putra Bangsa Purwosari melalui Strategi Optimalisasi Monitoring Kepuasan Peserta Didik - Fifi Arisanti Ocha (Elsalima (Salam Institute), 2024)
In this community service project, the focus was placed on improving the quality of educational services at KB PKK Putra Bangsa Purwosari through the strategy of optimizing student satisfaction monitoring. The methods used involved student satisfaction surveys, data analysis, and the implementation of continuous improvements. The results of the project showed a significant increase in student satisfaction levels and an improvement in the efficiency of educational services. The conclusion of this community service emphasizes that continuous monitoring of student satisfaction is a crucial element in enhancing the quality of services at KB PKK Putra Bangsa Purwosari. These findings provide guidance for educational institutions in optimizing their educational services.